2005
DOI: 10.1111/j.1551-2916.2005.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Titanium Carbonitride Phases by Reactive Milling of the Elemental Mixed Powders

Abstract: Titanium carbonitride (TiC x N 1Àx ) powders were obtained by high-energy ball milling of elemental titanium and carbon (activated carbon or graphite) in a nitrogen atmosphere. The formation of the carbonitride phase was controlled by adequately choosing the experimental conditions of the milling process. The stoichiometry of TiC x N 1Àx powders was modified by adjusting the titanium-to-carbon molar ratio. The composition and cell parameters of the carbonitride phases were determined. Microstructural character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
5
39
0
Order By: Relevance
“…However, the C and N contents obtained by elemental analysis showed that the carbonitride phase was deficient in nitrogen with a chemical formula of Ti 0.8 Ta 0.1 Nb 0.1 C 0.5 N 0.3 . This result was in agreement with our previous studies on the synthesis of transition metal carbonitrides by MSR [9,[35][36][37], wherein carbonitride phases with C/N ratios slightly above the nominal stoichiometry according to the starting mixture were always obtained. Note that carbides and nitrides, and therefore carbonitrides, of groups IV and V transition metals are well known nonstoichiometric compounds with extended homogeneity intervals [38].…”
Section: Resultssupporting
confidence: 93%
“…However, the C and N contents obtained by elemental analysis showed that the carbonitride phase was deficient in nitrogen with a chemical formula of Ti 0.8 Ta 0.1 Nb 0.1 C 0.5 N 0.3 . This result was in agreement with our previous studies on the synthesis of transition metal carbonitrides by MSR [9,[35][36][37], wherein carbonitride phases with C/N ratios slightly above the nominal stoichiometry according to the starting mixture were always obtained. Note that carbides and nitrides, and therefore carbonitrides, of groups IV and V transition metals are well known nonstoichiometric compounds with extended homogeneity intervals [38].…”
Section: Resultssupporting
confidence: 93%
“…The synthesis of ternary carbonitride phases that could be employed as master alloys has been realized via different methods, such as thermal treatments [11], self-sustaining hightemperature synthesis [12][13][14][15][16], or mechanochemical synthesis [17,18]. Mechanochemical synthesis, which uses mechanical energy to generate chemical reactions and phase transformations, is 1 32 45 TiV111 Ti/V/C 1/1/1 54 64 TiTa111 Ti/ Ta/C 1/1/1 33 60 TiHf111 Ti/Hf/C 1/1/1 60 90 TiZr312 Ti/Zr/C 3/1/2 50 60 TiV312 Ti/V/C 3/1/2 53 63 TiTa312 Ti/Ta/C 3/1/2 43 53 TiHf312…”
Section: Introductionmentioning
confidence: 99%
“…As a promising alternative to the conventional methods, mechanically induced self-sustaining reactions (MSRs) have been employed to produce a variety of advanced materials including borides, carbides, nitrides, sulfides, hydrides, silicides, carbonitrides, intermetallics, etc. [5][6][7][8][9][10] Although the preparation of the carbides [11][12][13][14][15] and nitrides [16,17] of transition metals (especially those in groups IVB and VB) by MSR has been investigated, research is comparatively lacking on the direct formation of the carbonitrides of transition metals through combustion synthesis and has focused largely on the synthesis of titanium carbonitrides [18]. In addition to Ti(C,N), Córdoba and coworkers [6,8,9] recently conducted a SERIESs of experimental studies on the formation of Nb, Ta, Hf, (Ti, Nb), (Ti, Ta), (Ti, Zr), (Ti, V) and (Ti, Hf) carbonitrides by MSR using a powder mixture of metals and graphite under a nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%